Závislost cen akcií ropných společností na ceně ropy - Šoba, Oldřich; Širůček, Martin; Havíř, Tomáš (Vysoké učení technické v Brně, Fakulta podnikatelská, 2013)
Purpose of the article: The focus of this article is the relationship between selected oil company’s stock price and oil price and the dependence of these companies stock price on oil price in the period from year 2000 to 2010. Scientific aim: The aim of this paper is pursuant to partial empirical analysis evaluate the dependence of oil producer company’s stock price on oil price. The partial aim is identify the differences between oil price and stock price of selected companies by using two basic methodological procedures. The last goal is identify the relationship between stock price of each other selected companies. Methodology: The methodology used in this paper is based on the quantification of relationship between company’s stock price and oil price. Used methods are ADF unit root test which testing stationary of selected time series and the correlation analysis of between selected companies each other and between company’s stock price and oil price. The last is the Granger causality test, that is provided by several lags. The time series is from August 2000 to December 2010, that is meaning round 2.500 observations. Findings: According to empirical analysis was confirmed that between oil company’s stocks price and oil price is strong structure and that the oil price affect the stock price of selected companies. The reaction of stock price on the oil price movement is general between 5 and 9 days. The strongest relationship between oil price and stock price was find by the Chevron and Petroleo Brasiliero. Other site the weakness relationship was find by the BP company. Conclusions: The most discuss problem is right set the lag length. In this case was the lag set on 10 day and closer analysis was made for lag from 1 to 10 days. Another limits is the time frequency. The place for updating this study is use a minute or hour frequency for the time series. Another possibility for updating is closer analysis of selected time period e.g. US invasion into Iraq, or BP ecological catastrophe 2010.
The Dependence of Oil Company’s Stock Price on Oil Price
Keywords: crude oil; stocks; oil companies; the correlation matrix; Granger causality test